Child poverty and changes in child poverty in rich countries since 1990 - Wen-Hao Chen; Miles Corak (Luxembourg Income Study (LIS), 2005)
This paper documents levels and changes in child poverty rates in 13 OECD countries using data from the Luxembourg Income Study project, and focusing upon an analysis of the reasons for changes over the 1990s. The objective is to uncover the relative role of income transfers from the state in determining the magnitude and direction of change in child poverty rates, holding other demographic and labour market factors constant. As such the paper offers a cross-country overview of child poverty, changes in child poverty, and the impact of public policy in North America and Europe.
Keywords: 330; Armut; Kinder; Sozialpolitik; OECD-Staaten